The susceptibility of the lacewing butterfly, Cethosia Biblis Insularis C & R Fedler (Nymphalidae Lepidoptera) to cry 1 AB protein - Cayabyab, Bonifacio F.; Gonzales, Pablito G.; Cuaterno, Wilma R.; Siegfried, Blair D.; Sumalde, Augusto P.; Belen, Josemari M.; Ardes, Karen; Alcantara, Edwin P. (2011)
There are very few studies in the Philippines related to the risk assessment of Bt corn to non target organisms. The lacewing butterfly Cethosia biblis insularis C & R Felder is a non target organism and an uncommon butterfly present in riparian areas (land immediately surrounding water source) where Bt corn is planted. It feed on flowers where Bt corn pollen are deposited during pollen shedding. This study was conducted at NCPC-CPC Plant Quarantine Support Laboratory from January 2009 to May 2010 to find out the effect of Cry 1 Ab protein on the lacewing butterfly. Bioassay using the maximum hazard dose (i.e. approximately 10x the maximum Cry 1 Ab protein in Bt corn) was done. The estimate amount of Cry 1 Ab protein in Bt corn pollen is 0.09 mg/g pollen. Whole leaves of Adenia zucca, the host plant of lacewing butterfly were soaked in Cry 1 Ab protein and dried. Another set of leaves were dipped in 0.1 M carbonated buffer and these served as control group. Ten three day-old larvae were exposed per leaf. Nine trials of 450 treated larvae and 450 non-treated larvae were done. The percentage mortality range for the treated group was 0-10% with the mean of 3.11%. The percentage mortality range for the control group was 0-14% with a mean of 1.56%. The range of weight in grams of the treated group was 0.016-0.053 with a mean of 0.035 while the control group has 0.11-0.045 with a mean of 0.033, respectively. Differences on mean mortality and mean weight of treated control leaves using t-test with computed values of 0.704 and 0.315 were not significant. Hence, the Cry 1 Ab protein was not toxic to the lacewing butterfly.
Keywords: BT corn; Butterflies; Risk assessment; Host-parasite relationships